Greenspace spatial characteristics and human health in an urban environment: An epidemiological study using landscape metrics in Sheffield, UK. (November 2019) - Mears, Meghann; Brindley, Paul; Jorgensen, Anna; Ersoy, Ebru; Maheswaran, Ravi
Graphical abstract: Highlights: Landscape metrics demonstrate utility in linking greenspace patterns to human health. Multi-model inference identifies important metrics despite small effect sizes. Water cover, tree planting diversity are compositional characteristics that promote health. Large, interspersed greenspace patches are configurational characteristics that promote health. Abstract: Cross-sectional research linking exposure to greenspace with human health rarely describes greenspace characteristics in detail, but a few studies do find that some types of greenspace have greater health benefits than others. We review literature linking landscape metrics to multiple mechanisms by which greenspace exposure is posited to benefit health. Using metrics identified in this process to describe the composition and configuration of urban greenspace, we conduct a small-area epidemiological analysis of self-reported general health for the city of Sheffield, UK. A relatively high proportion of water cover and a high diversity of tree planting are associated with lower levels of poor health; while a high proportion of grass cover, which may be indicative of low quality greenspaces, is associated with higher levels. The presence of large greenspace patches that are well interspersed with the built environment is also associated with lower levels of poor health. We demonstrate a successful methodology for identifying useful landscape metrics even where effect sizes are small, and explore the challenges of translating results of landscape metric studies into policy guidance.